Corporate Criminal Liability in Procurement Activities within Corruption Offenses - Suhardi Somomoeljono; Saurav Kumar (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study analyzes the framework of corporate criminal liability in corruption offenses related to goods procurement. As corporations increasingly participate in public procurement processes, the potential for corrupt practices such as bribery, bid-rigging, collusion, and fraudulent documentation poses significant risks to the integrity of government contracting. This research examines the legal basis for holding corporations criminally accountable, including the criteria for attributing criminal acts to a corporate entity, forms of liability, and applicable sanctions under Indonesian anti-corruption law. The study also reviews relevant judicial decisions to assess how courts interpret and apply corporate liability in procurement-related corruption cases. The findings indicate that although corporate criminal liability is formally recognized, challenges persist in proving corporate intent, identifying responsible managerial roles, and ensuring consistent judicial interpretation. The study concludes that strengthening compliance systems, improving procurement oversight, and providing clearer regulatory guidelines are crucial to enhancing the effectiveness of corporate criminal liability in corruption cases involving goods procurement.